Prospective comparative study of laparoscopic totally extraperitoneal versus Lichtenstein’s tension free open meshplasty for management of inguinal hernia - Patel, Digant A.; Vaghasiya, Govardhan N.; Patel, Jagrutkumar R. (International Surgery Journal, 2020)
Background: Since the advent of minimal access surgery, its application has been widespread starting from appendectomy to complex intestinal surgeries carried out laparoscopically. But hernia surgery is a major debatable section, to compare it with the commonly performed gold standard Lichtenstein repair. First laparoscopic transabdominal preperitoneal and then totally extra peritoneal (TEP) repair came into existence. In today’s era of extended TEP repair laparoscopic TEP repair has emerged to be gold standard. Methods: This is a prospective cohort study including 40 cases of Lichtenstein open meshplasty, against minimally invasive laparoscopic TEP procedure were compared. Patients operated in our department between January 2010 and September 2010 were included after consent and assessment. Procedures were carried out according to standard guidelines, and results compared for technical details, cosmesis, intra or post-operative complications, analgesia requirement, hospital stay, recovery and follow up and all results were analyzed. Results: Operative time was less by 2 minutes, hospital stay less by 1 day, return to work earlier by nearly 20 days for strenuous work, analgesia requirement less for laparoscopic extra peritoneal repair. Conclusions: Study showed that if the period of learning curve has been eliminated than an experienced surgeon performs laparoscopic procedure with better patient satisfaction, less hospital stay, faster recovery and earlier return to work with less operative time, analgesic consumption, and complication.